Optical tweezer induced by microring resonator - Abd. Aziz, Muhammad Safwan (2013)
Optical tweezer technique for molecular trapping is becoming of increasing importance for numerous biological applications. The main objective of this study was to investigate the dynamical behavior of the optical tweezers signals in microring resonators (MRR). Operating system consists of modified nonlinear adddrop optical filter made of InGaAsP/InP integrated together with a series of nonlinear nanoring resonators. This particular form is known as a PANDA ring resonator. Different models of operating system were designed and optical transfer functions for each model were derived by using Z-transform method. Simulation results were obtained from MATLAB2010a program by using parameters of practical devices. Input signals in the form of dark soliton were generated at center wavelength 1.5 µm with peak intensity 1 W/?m2 and pulse width 50 ps. Radii of rings were set to be R=34 µm, R1=60 nm, R2=60 nm, R3=50 nm and R4=50 nm respectively. Coupling coefficients of the system were chosen to be ?1=0.15, ?2=0.65, ?3=0.5, ?4=0.5, ?5=0.5 and ?6=0.50. Intense output signals in the form of potential well are generated at the intensity of 219.14 W/?m2 and FWHM around 20 nm. Simulated results shows an optical force of 15.83 fN generated from intensity gradient associated with the output signal are calculated for particle of diameter 20 nm. Stiffness at the center of the trap was recorded at 2.23 fN nm-1. This study shows that the model was able to control the dynamical behavior of optical tweezers. Analytical formulation of such system provides the underlying physics of dynamic optical tweezers generation within MRR.